A Binary Particle Swarm Optimization (BPSO) algorithm to solve a reverse logistics supply chain problem. (2014) - Santibanez-Gonzalez, Ernesto Del R.; Montoya-Torres, Jairo R.; Huatuco, Luisa Huaccho
No abstract available